Chemical Pretreatment and Enzymatic Saccharification of Seaweed Solid Wastes - Pujoyuwono Martosuyono; Andi Hakim; Yusro Nuri Fawzya (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2015)
The technical feasibility of seaweed waste utilization as a resource of renewable energy was investigated in this paper. The production of fermentable sugars from seaweed waste was studied by dilute sulfuric acid and sodium hydroxide pretreatment and further enzymatic hydrolysis. Pretreatment was conducted by using 1.0 and 2.0% dilute sulfuric acid w/v and 4 and 5% sodium hydroxide w/v for 30 min at 121 oC. Pretreated seaweed wastes were analyzed by XRay Diffraction (XRD) to examine the crystallinity index of the cellulose and observed using Scanning Electron Microscopy (SEM) to examine the changes in structure of cellulose fiber. Saccharification of pretreated seaweed waste was carried out using crude cellulase enzyme provided by Pulp and Paper Research Center in Bandung. Saccharification was done in shake flask with 20% of substrate in citrate phosphate buffer at 30 oC and 50 oC, agitation of 150 rpm in shaking incubator for 48 h. Samples were collected at 2, 6, 12, 24 and 48 h for further analysis. Enzyme concentrations were varied between 1050 U/g dry samples. The results showed that dilute acid and base pretreatment of seaweed solid waste can be used to improve the digestibility of seaweed waste. It successfully acted by reducing the lignin content and degrading the structure of cellulose from crystalline into amorphous form which is more susceptible to the enzyme action.The optimum pretreatment condition was shown by 4% NaOH at 121 oC for 30 min, producing the most fermentable sugar concentration. Sugar concentration produced by saccharification was optimum at 50 oC, enzyme concentration of 50 U/g sample for 24 h base pretreatment. The results of the experiment were expected to contribute in the process development of bioconversion of lignocellulosic materials into renewable energy sources.